An elastic–plastic damage model considering capillary effect for petrol–water saturated sandstone. (November 2018) - Yang, HQ; Liu, JF; Luo, C; Zhou, XP
The mechanical behavior of surrounding rock mass is key important to the water-sealed petrol storage caverns because of the two phase environment. To investigate the strength and damage mechanism of rock mass under petrol–water immersion circumstance, an elastic–plastic damage constitutive model is proposed. The deformation work of rock mass is derived according to the mixture theory and averaging methods. In order to further study the capillary action influence of petrol–water liquid phase on the strength and stiffness of rock mass, the plastic yield condition considering petrol–water circumstance is proposed. Then, the stress–strain increment expression under the influence of both liquid and solid phase is deduced through the consistency condition. Meanwhile, the damage conditions of the rock mass under tensile and compressive stress differ a lot, so the rock mass damage model under petrol–water circumstance is established combining the tensile and compressive damage criterion and the damage evolution law. The proposed constitutive model is adopted to simulate the mechanical property and damage evolution feature of rock mass under axial compression. The results suggest that the increase in the petrol pressure leads to the improvement of the axial strength for rock mass and meanwhile, the occurrence of damage is also advanced. In addition, the elastic–plastic property of the rock material has been well developed below the stress peak point during this process. Ultimately, the proposed elastic–plastic damage constitutive model was verified by making comparisons between the theoretical calculating results and experimental results.